A realistic and future outlook for developing some of the pillars of the colleges of education in Iraq - Nidal Muzahim Rashid Al-Azzawi (Zanco Journal of Humanity Sciences)
The process of re-development of colleges of education has become an urgent necessity in most countries of the world, including in Iraq, especially after the emergence of variables and the existence of reasons for development, including "population growth, changes in political systems and their philosophy, and external cultural influences", as well as the educational challenges facing education, and perhaps Among the most important of these challenges are the following: economic challenges such as (the high cost of education, the labor market and educational outcomes, and insufficient funding allocated to educational institutions), social challenges such as (increasing population growth rates, globalization, accompanying challenges and changes in the family climate), and technical challenges such as (He introduced educational curricula, the lack of professional and training growth programs for teachers, and the centralization of educational decision-making), and technological challenges such as (the emergence of modern technologies, the emergence of modern means of mass communication such as the information network, the educational iPad, electronic book ... etc.). All of these challenges and many more have made the process of developing Faculties of Education inevitable.